1011 Introducing Video as a Supplement in the Assessment of Student Performance in Clinical Pediatric Examination. (October 2012) - Malon, M; Cortes, D; Greisen, G; Simonsen, H; Sørensen, JL; Andersen, J; Nygaard, U; Poulsen, A; Mortensen, HB
Abstract : Background and Aims: It is time consuming to include patients in the clinical pediatric examination of medical students. At Copenhagen University we perform a 25 min oral examination, based on a clinical paper case and wanted to evaluate supplemental exam questions, based on video. Methods: With written parental consent 17 videos lasting 30 seconds were recorded, demonstrating children with common clinical conditions. After the case-based examination, the student blindly chose one of the videos and was allowed to see the video twice, before assessing the specific symptoms and general appearance of child. After the examination, the internal and external examiner answered a simple questionnaire. Results: 141 students were examined using videos. The videos were rated as suitable by 89%(92/103) of the internal examiners and by 76%(78/103) of the external examiners (Fishers Exact test, p<0.05). Overall, the internal and external examiners rated the video part on a 5-point Likert scale to be important or very important in 38%(40/106) and 36%(37/103) of the exams, respectively (Fishers Exact test, p=0.886). The internal examiners reported, that the video had changed the grades in 40%(42/106) of the exams, which was similar to 37%(38/103) for external examiners (Fishers Exact test, p=0.776). Overall the grades at the examination were unchanged, median B (range G to A), n=117 before and median B (range F to A), n=141 (Mann-Whitney test, p=0.992) after videos were included. Conclusions: A short video showing a child with a common clinical condition appears to contribute significant to an oral examination based on a paper case.